The Dilemma of Establishing a Land Bank Institution: Social Equality or Economic Growth? - Prianggoro, Afwan Anantya; Pramono, Retno Widodo Dwi (TEMALI : Jurnal Pembangunan Sosial, 2023)
Indonesia's main land management agenda is agrarian reform, consolidating and distributing land for equity and social justice. In addition to strengthening existing institutions, Indonesia established a land bank whose main task is to provide land for investment and economic purposes. For some people, the goals of land banks interfere with land management practices in Indonesia because they are at odds with the goals of agrarian reform. So the research question that needs to be answered is what are the advantages and disadvantages of land bank practices in Indonesia? This research aims to identify the advantages and disadvantages of land bank practices in Indonesia. By identifying the advantages and disadvantages of land bank practices, the output of this study is expected to provide recommendations to improve the quality of land bank policies. This is a case study research with a qualitative approach using descriptive analysis. The data source comes from the secondary data. The study results show that establishing a land bank has one of the advantages in solving land, environmental, and spatial planning problems. Meanwhile, the weakness of the practice of land banks in Indonesia is the potential for being unconstitutional and over-authorized. Thus, from the findings of weaknesses in the practice of land banks, recommendations are made for the government to clarify the functions and objectives of land banks to improve the social and economic welfare of the Indonesian people.